Work-Related Injuries Resulting in Death in Chile: A Cross-Sectional Study on 2014 and 2015 Registries - Bachelet-Norelli, V (BMJ Publishing Group, 2018)
Objective: To characterise work-related fatal events that occurred in Chile in 2014 and 2015 in workers covered by the Occupational Accidents and Professional Disease No 16.744 Act. Design: Cross-sectional on registries of the Chilean Worker s Health and Safety National Information System, specifically focusing on the Fatal Work Accidents Registry of the Social Security Superintendence. Study population: Secondary data analysis on all 815 cases of occupational injury-related deaths registered in 2014 and 2015 in Chile and that were accredited by the Social Security Superintendence up to March 2016. Outcome measures: Variables relating to employer, workers and the events were analysed. Results: The overall mortality rate for all injuries, both at work and during commuting, per 100 000 workers affiliated to the occupational social security system, was 7.2 for 2014 and 7.3 for 2015. For 2014, the highest mortality rates occurred in the transport and communications sectors (20.15) and the mining sector (18.17), while for 2015 the highest rates were found in the fishing industry (11.3) and in mining (12.1). Seventy-two per cent of cases occurred in small and medium-sized enterprises. Half of the companies that had work-related fatal injuries did not have a risk prevention department. Twenty-two per cent (121) of the companies had previous labour law infractions. The four activities most affected by workers deaths in the two study years were freight land transport, engineering works under construction, minor works under construction and construction of complete buildings or parts of buildings. Half of all fatal injuries occurred in workers who had been employed for less than a year in their company. Conclusions: This descriptive study provides valuable insight into the current national registry on occupational deaths in Chile. While containing valuable information, the registry was not designed for epidemiological surveillance. Further efforts are needed to achieve a proper epidemiological integration of surveillance data. © 2018 Article author(s).
Keywords: injuries; mortality; occupational; work related